Pengaruh Dana Bantuan Produktif Usaha Mikro, Intellectual Capital Dan Perangkat Lunak Akuntansi Terhadap Kinerja Usaha Mikro Kecil Menengah - Teguh Purwanto; Rini Hidayah; Djauhar Edi P; F Fatkhurrokhmah (Neraca, 2022)
This study aimed to determine the effect of (1) Micro Business Productive Assistance Fund, (2) Intellectual Capital, and (3) Accounting Software on the Performance of Micro, Small, and Medium Enterprises (MSMEs) (4) either partially or simultaneously. The population of this study were MSMEs registered at the Office of Trade, Cooperatives and MSMEs of Pekalongan in 2020-2021. The samples were 100 respondents, selected through a purposive sampling technique. This study employed a multiple linear regression analysis with the help of SPSS version 16. The results of the study showed that: (1) the Productive Assistance Fund for Micro Businesses had a significant effect on the performance of MSMEs; (2) the Intellectual Capital had a significant effect on the performance of MSMEs; and (3) the Accounting Software had a significant effect on the performance of MSMEs, (4) the Productive Assistance Funds, the Intellectual Capital, and the Accounting Software had a significant effect on the performance of MSMEs simultaneously. Keywords: performance of MSMEs, Micro Business Productive Assistance Fund, Intellectual Capital, and Accounting Software